Associations between longitudinal serum perfluoroalkyl substance (PFAS) levels and measures of thyroid hormone, kidney function, and body mass index in the Fernald Community Cohort. (November 2018) - Blake, Bevin E.; Pinney, Susan M.; Hines, Erin P.; Fenton, Suzanne E.; Ferguson, Kelly K.
Abstract: Perfluoroalkyl substances (PFAS) are a diverse class of manufactured compounds used in a wide range of industrial processes and consumer products and have been detected in human serum worldwide. Previous cross-sectional and cohort studies in humans have suggested exposure to PFAS is associated with a wide array of chronic diseases, including endocrine disruption, developmental health effects, cancer and metabolic changes. We examined the associations between a panel of eight PFAS and indicators of thyroid disruption, kidney function, and body mass index (BMI), all of which were measured at repeated time points (1990–2008) over the course of the study. Participants (N = 210) were selected from the Fernald Community Cohort based on household water supply from a PFAS-contaminated aquifer. In adjusted repeated measures models, we observed several notable associations between serum PFAS and thyroid hormones as well as kidney function as measured by estimated glomerular filtration rate (eGFR). An interquartile (IQR) increase in serum PFOS was associated with a 9.75% (95% CI = 1.72, 18.4) increase in thyroid stimulating hormone. An IQR increase in serum PFNA, PFHxS, and PFDeA was associated with a −1.61% (95% CI = −3.53, −0.59), −2.06% (95% CI = −3.53, −0.59), and −2.20% (95% CI = −4.25, −0.14) change in eGFR, respectively. On the other hand, an IQR increase in serum Me-PFOSA was associated with a 1.53% (95% CI = 0.34, 2.73) increase in eGFR. No significant associations with BMI and serum PFAS were noted. Our findings are in agreement with previous reports that serum PFAS are associated with altered kidney and thyroid function. Graphical abstract: Image 1 Highlights: Repeated measures of serum PFOS are associated with increased thyroid stimulating hormone. Repeated measures of serum PFNA was positively associated with Total T4 in women. Repeated measures of serum PFNA, PFHxS, and PFDeA are associated with decreased kidney function. PFHxS retained high stability between serum measurements over a period greater than 10 years.